Drop printing of pharmaceuticals: Effect of molecular weight on PEG coated‐naproxen/PEG 3350 solid dispersions. Issue 12 (14th August 2015) - Hsu, Hsin‐Yun; Harris, Michael T.; Toth, Scott; Simpson, Garth J.
Abstract : Solid dispersions have been used to enhance the bioavailability of poorly water‐soluble active pharmaceutical ingredients (APIs). However, the solid‐state phase, compositional uniformity, and scale‐up problems are issues that need to be addressed. To allow for highly controllable products, the drop printing (DP) technique can provide precise dosages and predictable compositional uniformity of APIs in two‐/three‐dimensional structures. DP was used to prepare naproxen (NAP)/polyethylene glycol 3350 (PEG 3350) solid dispersions with PEG coatings of different molecular weights (MWs). A comparison of moisture‐accelerated crystallization inhibition by different PEG coatings was assessed. Scanning electron microscopy, second harmonic generation microscopy, and differential scanning calorimetry analysis were performed to characterize the morphology and quantify the apparent crystallinity of NAP within the solid dispersions. Thermogravimetric analysis was employed to measure the water content within each sample. The results suggest that the moisture‐accelerated crystallization inhibition capability of the PEG coatings increased with increasing MW of the PEG coating. Besides, to demonstrate the flexibility of DP technology on manufacturing formulation, multilayer tablets with different PEG serving as barrier layers were also constructed, and their dissolution behavior was examined. By applying DP and appropriate materials, it is possible to design various carrier devices used to control the release dynamics of the API. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4502–4508, 2015